UPAYA MENINGKATKAN MINAT BELAJAR SISWA DENGAN MEDIA BELAJAR BENDA KONKRET KELAS 3 PADA MATA PELAJARAN MATEMATIKA DI UPTD SD NEGERI 2 METRO TIMUR - Alvina Anggun Putriani; Putri Nur Utami; Thirani Anggieta Putri; Finorina; Roli Fola Cahya Hartawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to enhance the interest and learning outcomes of third-grade students at SD Negeri 2 Metro Timur in Mathematics through the use of concrete objects as learning media. The research employed a Classroom Action Research (CAR) method conducted collaboratively n two cycles. Data were collected through observations and tests (pre-test and post-test) and analyzed using descriptive quantitative and qualitative approaches. The results showed a significant improvement in students' learning outcomes. The pre-test average score was 60.41, with a mastery percentage of 41.6%, where as the post-test average increased to 81.87, with a mastery percentage of 83.3%. The use of concrete objects proved to be effective in increasing students' interest in learning, positively impacting their understanding of the material and academic performance. Therefore, innovative learning media such as concrete objects can serve as a solution to improve classroom learning quality